THE CHALLENGES OF REGIONAL AUTONOMY AND FOREIGN INVESTMENT IN PAPUA (1998-2019) - Adri Arlan (JISOS: JURNAL ILMU SOSIAL, 2022)
The implementation of Papua’s special autonomy (Otsus) that is written in Law No.21 in 2001 has a significant role to local governments. Policies are aiming to develop the local people of Papua (OAP) as well. However, the number of inequalities among OAP are still on high number. The research try to analyze and identify the problems based on literature review and public policy effectiveness from local and central government in The Papua.